Pengaruh Brand Image dan Influencer Marketing terhadap Keputusan Pembelian Konsumen melalui Minat Beli sebagai Variabel Intervening: Studi pada Followers Akun TikTok @Skintific_id - Nabila, Jihan; Azijah, Nur (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The sales increase of Skintific products decreases in the April period and increases in the July period in 2022, and continues to increase from year to year. Influencer marketing can also be used as an appropriate marketing strategy to increase sales results and promote products widely. This is because influencers have the ability to give the public confidence in the image of a product, so with this ability it is able to influence the purchase decision of a particular product by customers. The purpose of this study is to determine "The Effect of Brand Image and Influencer Marketing on Consumer Purchase Decisions Using Purchase Intention as an Intervening Variable (Study of Followers of the TikTok @Skinyific_id Account)". The data collection method uses a questionnaire with a quantitative approach. The sampling method uses purposive sampling, which is a sampling technique where the person selected as a sample is in accordance with the purpose of the research, the sample used is 100 respondents. The data analysis technique used is path analysis technique through SPSS 16 program. The results indicated that brand image and influencer marketing variables had a positive and significant effect on purchase decisions through purchase intention as an intervening variable.